2012
DOI: 10.1016/j.abb.2012.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of N-terminal mutants of Connexin 32 using 1H NMR spectroscopy

Abstract: The amino terminus of gap junction proteins, connexins, plays a fundamental role in voltage gating and ion permeation. We have previously shown with 1H NMR that the structure of the N-terminus of functional connexin molecules contains a flexible turn around G12 (Arch. Biochem. Biophys.490:9,2009) allowing the N-terminus to form a portion of the channel pore near the cytoplasmic entrance. The mutants of nonfunctional connexin molecules G12S and G12Y were found to prevent this turn. Previous functional studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…These studies demonstrated the presence of a flexible open turn initiated by the 12th residue (glycine in both Cx26 and Cx32) that would allow the n-terminal half of the N-terminus to be positioned within the channel pore. 53 , 54 , 55 Demonstration that cysteine substitutions of the 4th, 5th, and 8th position can be modified by a MTS reagents strongly support the proposed structure 14 and Oh and Bargiello (unpublished observations). Significantly, the NMR derived structure agrees well with that of the N-terminus in the crystal structure of Cx26 gap junctions.…”
Section: Voltage Regulation Of Connexin Channel Conductancesupporting
confidence: 53%
“…These studies demonstrated the presence of a flexible open turn initiated by the 12th residue (glycine in both Cx26 and Cx32) that would allow the n-terminal half of the N-terminus to be positioned within the channel pore. 53 , 54 , 55 Demonstration that cysteine substitutions of the 4th, 5th, and 8th position can be modified by a MTS reagents strongly support the proposed structure 14 and Oh and Bargiello (unpublished observations). Significantly, the NMR derived structure agrees well with that of the N-terminus in the crystal structure of Cx26 gap junctions.…”
Section: Voltage Regulation Of Connexin Channel Conductancesupporting
confidence: 53%
“…N-terminal peptides with mutations that fail to form a flexible turn do not form functional channels [25, 26]. The solution structure of the Cx26 N-terminal G12R peptide indicates formation of a highly flexible open turn, whereas that of Cx32G12R forms a highly structured more constrained turn.…”
Section: Resultsmentioning
confidence: 99%
“…Our past studies have shown that formation of an open flexible turn in Cx32 N-terminal peptides correlates with channel expression. Cx32 peptides containing substitutions G12S, Y7D and W3D do not form the open turn initiated by G12 and these mutations fail to produce functional channels [25, 26, 54]. In the case of G12S, the loss of expression is a consequence of a trafficking/assembly defect [19], and it is likely that the same is true for Y7D and W3D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short NH 2 -terminal domains of the six Cx subunits form the funnel-shaped channel wall (FIGURE 2C), which is stabilized and held in place by a circular network of hydrogen bonds formed between the D2 residue on one Cx subunit and the backbone amide of T5 on another Cx subunit, as well as between W3 and M32 in TM1 within the same Cx subunit; yet the crystallographic data indicate that the NH 2 termini are the most mobile domains in the Cx26 channel structure. Indeed, the secondary structure of the NH 2 terminus can be broken down into two regions: an NH 2 -terminal ␣-helix or hydrophobic domain followed by an open turn (FIGURE 2A, (81), NH 2 -terminal FPtagged GJ channels are nonfunctional based on their inability to transfer the GJ-permeable dye lucifer yellow (99). Thus, although NH 2 -terminal GFP-tagged Cxs may be useful to address certain questions (11,23,27,60), their inability to form functional channels may be as destructive as the inability of COOH-terminal GFP-tagged Cxs to bind to the scaffolding protein ZO-1 (73) (see Cx43/ ZO-1 Binding for more detail), and this needs to be taken into close consideration if meaningful results are to be obtained.…”
Section: The 3d Structure Of a Gj Channel Provides Functional Cues Rementioning
confidence: 99%